Scaling theory for liquid propellant rocket thrust chambers - Sethna, C. M. (Defence Science Journal, 2014)
With the advent of the very large liquid propellant rocket, it has become necessary, if possible, to derive a rational scaling theory for combustion chamber design so as to enable relatively simple and economical initial tests to be carried out on small scaled models using scaled parameters of propellant mass flows, pressure etc., and from these to predict operating and design data for the full scale rocket. Owing to the complex and interdependent nature of the aerothermo-chemical processes in the chamber involving evaporation, diffusion and chemical reaction, the similarity criteria must necessarily extend over several, non-dimensional parameters, but it is still possible to evolve relatively simple rules for correlating the design and performance of the model and large scale motors-as shown by Penner-Tsien and Crocco. The paper concludes with a discussion of the accuracy and practical feasibility of such scaling rules.